Trignometric identities question

Asked by  | 5th Oct, 2008, 09:10: PM

Expert Answer:

taking Lcm and solve we get     sin2Φ(1-sin2θ)2 + sin4θcos2Φ = sin2Φ (1-sin2Φ )

further solving in terma of sinΦ and sinθ       we get    sin4θ + sin4Φ  = 2sin2Φ sin2θ                                           which gives (sin2θ - sin2Φ)2 =0   =====> sin θ  =  sinΦ   ===> θ =  Φ 

so putting θ =  Φ in second eqn. we get  sin2θ + cos2θ = 1    which is true

Answered by  | 16th Dec, 2008, 10:04: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.